Clinical research Value of α-smooth muscle actin and glial fibrillary acidic protein in predicting early hepatic fibrosis in chronic hepatitis C virus infection - Zakaria, Sohier; Youssef, Magdy; Moussa, Mona; Akl, Maha; El-Ahwany, Eman; El-Raziky, Maysa; Mostafa, Omaima; Helmy, Ahmed-Hazem; El-Hindawi, Ali (Archives of Medical Science, 2010)
Introduction: α-Smooth muscle actin (α-SMA)-positive hepatic stellate cells (HSCs) are pericytes responsible for fibrosis in chronic liver injury. The glial fibrillary acidic protein (GFAP), commonly expressed by astrocytes in the central nervous system, is expressed in vivo in the liver in a subpopulation of quiescent stellate cells. The reports concerning GFAP expression in human liver are still conflicting. The aim of the study is investigation the utility of GFAP compared to α-SMA as an indicator of early activated HSCs, in predicting fibrosis in chronic hepatitis C (CHC) patients. Material and methods: With immunohistochemistry and a semi-quantitative scoring system, the expressions of α-SMA and GFAP on HSCs in liver biopsies from patients with pure CHC (n = 34), hepatitis C virus-induced cirrhosis (n = 24), mixed CHC/schistosomiasis (n = 11) and normal controls (n = 10) were analysed. Results: The immunoreactivity of α-SMA and GFAP in perisinusoidal, periportal and pericentral areas was assessed. α-Smooth muscle actin and GFAP-positive HSCs were significantly increased in all diseased groups compared with normal controls. In pure CHC with or without cirrhosis, perisinusoidal α-SMA-positive HSCs were predominant in relation to GFAP-positive cells. On the other hand, GFAP-positive cells were predominant in the group of schistosomiasis as compared with the other diseased groups. It was noticed that expression of GFAP on perisinusoidal HSCs in CHC patients sequentially decreased with the progression of fibrosis. Conclusions: Glial fibrillary acidic protein could represent a more useful marker than α-SMA of early activation of HSCs in CHC patients and seems to be an early indicator of hepatic fibrogenesis.